Intracavity folding of a perylene dye affords a high-affinity complex with cucurbit[8]uril. Issue 66 (2nd August 2017) - Aryal, Gyan H.; Assaf, Khaleel I.; Hunter, Kenneth W.; Nau, Werner M.; Huang, Liming
Abstract : We have designed a fluorescent perylene dye with two aromatic units for intracavity folding to afford a high-affinity complex with cucurbit[8]uril. The high affinity allows the complex to act as a fluorescent probe for detection of strong binding guests with nanomolar sensitivity. Abstract : A fluorescent perylene dye with two aromatic units was designed for binding to cucurbit[8]uril. The binding affinity of the complexes increased about 3 orders of magnitude compared to the dye without a secondary aromatic unit. The high affinity allows the complexes to act as fluorescent probes for detection of strong binding guests with nanomolar sensitivity.